Concept of Force Across Different Levels - SHARMA, S.V. (SCHOOL SCIENCE, 2007)
EXPLORATION of misconcepts of physics among students at various levels has been of much interest during the last few decades {Saxena (1996), Saxena (1997), Hake (2001), Savinainen and Scott (2002), Jain et al (2003), Barak (2004), Sharma and Sharma (2003), Sharma and Sharma (2004), Jadhao and Parida (2005) and Sharma (2005)}. Prior knowledge of the misconcepts among students can be the basis for generating discussion and planning of strategy to help the students acquire the correct concepts and also make them think in a scientific way. Since pre-conceived concepts have been found to be resistant to change, it is all the more important that they are identified and suitable strategies are employed in the classroom situation to handle them effectively. There are a large number of misconceptions prevailing amongst physics students including the concept of force even after studying physics for a number of years.